Validation of Satellite Estimated Solar Ultraviolet Radiation Data with Ground Based data in Kathmandu, Nepal - Sharma, Niranjan Prasad (Journal of the Institute of Engineering, 2016)
The main objective of this study is to validate the satellite estimated solar Ultraviolet radiation data with ground based data in Kathmandu (27.72 N, 85.32 E), located at an elevation of 1350m, from the sea level. The ground based measurement and the satellite estimation were performed by NILU-UV irradiance meter and EOS Aura OMI satellite respectively. The NILU-UV irradiance meter is a six channel 0 0 radiometer designed to measure hemispherical irradiances on a fat surface. Meanwhile the Ozone Monitoring Instrument (OMI) on board, the NASA EOS Aura space craft is a nadir viewing spectrometer that measures solar refected and back scattered light in ultraviolet and visible spectrum. The study is based on OMI and ground based (GB), Ultraviolet Radiation (UVR) data. Considering these data the relative differences between predicted OMI and ground based Ultraviolet Index (UVI) assuming normal distribution ±1σ was found to be 24.8±13.7% in July. Further study showed that the ratio of predicted OMI, UVI to that determined from ground based measurement is 1.14. Also the relative difference in UVI in corrected condition in summer season was found to be 5.8%. The correlation between predicted UVI and ground based UVI was found to be signifcant. Journal of the Institute of Engineering, 2015, 11(1): 101-107